PENGARUH PERTUMBUHAN EKONOMI DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PREVALENSI KETIDAKCUKUPAN KONSUMSI PANGAN DAN DISPARITAS PREVALENSI KETIDAKCUKUPAN KONSUMSI PANGAN - Dahiri (Pusat Kajian Anggaran, 2023)
The prevalence of undernourishment is one of the national strategic programs in the 2020–2024 national medium-term development plan, with a target of 5.38 percent in 2024. However, the prevalence of undernourishment during the 2017–2022 period shows an increasing trend amid growth, the economy is improving, and the unemployment rate is falling. The research method used is quantitative research with regression models, ANOVA tests, and Duncan tests. The data used are secondary data, namely economic growth, open unemployment rates, and the prevalence of undernourishment nationally and regionally during the 2017–2022 period. The results showed that economic growth and the open unemployment rate had no significant effect on the prevalence of undernourishment nationally and regionally, and there were significant differences in the prevalence of undernourishment between provinces in Indonesia, thus forming 14 disparity clusters.